Alterations of platelet functions in children and adolescents with iron-deficiency anemia and response to therapy. (July 2015) - Mokhtar, Galila M.; Ibrahim, Wafaa E.; Kassim, Nevine A.; Ragab, Iman A.; Saad, Abeer A.; Abdel Raheem, Heba G.
Abstract Several changes in platelets have been reported in patients with iron-deficiency anemia (IDA), so a relationship between iron metabolism and thrombopoiesis should be considered. We aimed to study the alterations of platelet functions in patients with IDA by assessment of platelet aggregation with epinephrine, adenosine diphosphate (ADP) and ristocetin and by measuring platelet function analyzer-100 (PFA-100) closure time together with the effect of iron therapy on the same tests. A follow-up study was conducted in Ain Shams University Children's hospital in the period from June 2011 to June 2012 including 20 patients with confirmed IDA and 20 healthy age- and sex-matched control. Bleeding manifestations were reported. Laboratory analysis included complete blood count, assessment of iron status by measuring serum iron, TIBC and ferritin, assessment of platelet functions by PFA-100 closure time and platelet aggregation with collagen, ADP and ristocetin. Patients with IDA were treated by oral iron therapy 6 mg/kg/day of ferrous sulfate and post-therapeutic re-assessment was done. Mean age of IDA patients was 5.7 ± 4.2 years. Bleeding manifestations were more common in patients group. Mean PFA-100 closure times (with epinephrine) were significantly longer in patients (179.1 ± 86.4 seconds) compared to control group (115 ± 28.5 seconds) (p < 0.05). Platelet aggregation by ADP (38.1 ± 22.2%), epinephrine (19.7 ± 14.2%) and ristocetin (58.8 ± 21.4%) were significantly reduced in patients compared to control (62.7 ± 6.2, 63.3 ± 6.9, 73.8 ± 8.3, respectively; p < 0.001). After treatment platelet aggregation tests induced by ADP (64.78 ± 18.25%), and epinephrine (55.47 ± 24%) were significantly increased in patients with IDA compared to before treatment (39.44 ± 21.85%, 20.33 ± 14.58%; p < 0.001). PFA-100 closure time as well showed significant decreased after treatment (118.4 ± 27.242) compared to before treatment (186.2 ± 90.35; p < 0.05). A negative correlation between platelet aggregation induced by ADP and mean values of serum ferritin before treatment (r = 0.042, p < 0.05) was found. A mutual effect is considered between iron deficiency and platelet functions. Subtle bleeding manifestations can occur in patients with IDA with delay in platelet aggregation and prolongation in PFA-100 closure times which can be reversed by iron therapy.